A phonetic case study of Tŝilhqot'in /z/ and /zʕ - Bird, Sonya; Onosson, Sky (Journal of the International Phonetic Association, 2022)
This research was conducted on the lands of the Tŝilhqot’in Nation (data collection), the Esquimalt, Songhees, and W̱SÁNEĆ Nations, and in Treaty One territory, original lands of the Anishinaabeg, Cree, Oji-Cree, Dakota, and Dene peoples, and the homeland of the Métis Nation. We are grateful to be able to live and work on these lands. We would like to thank the Tŝilhqot’in speakers who welcomed us into their homes and shared their language with us. We are also grateful to the audience members at the 2014 Phonetic Building Blocks of Speech conference, and to the two anonymous reviewers who provided us with such thorough and insightful feedback on our work. This paper provides an acoustic description of /z/ and /zʕ/ in Tŝilhqot’in (Northern Dene). These sounds are noted by Cook (1993, 2013) to show lenition and some degree of laterality in coda position. Based on recordings made in 2014 with a single, mother-tongue speaker of Tŝilhqot’in, we describe their acoustic properties and examine their distribution as a function of prosodic position and segmental environment. We find that they vary along three dimensions: manner (fricative–approximant), degree of retraction (non-retracted–retracted), and laterality (non-lateral–lateral). In addition, some tokens have a characteristic ‘buzziness’, which has been associated with the Chinese front apical vowel (Shao & Ridouane 2018, 2019) and the Swedish ‘Viby-i’ (Westberger 2019). We argue that ‘lenition’ (Kirchner 2004, Ennever, Meakins & Round 2017) can only account for some of the observed variation and suggest that both /z/ and /zʕ/ are specified for two tongue articulations: tongue tip/blade and tongue body (Laver 1994), encompassing laterality (and concomitant retraction) in addition to the primary coronal gesture. This work was funded by the Social Sciences and Research Council of Canada, grant # 410-2011-224. Faculty Reviewed